Business strategy, high involvement human resource management and firm performance : a study of small and medium enterprises in Malaysia - Wee Yu Ghee; Chin Hsien Yeen; Sapto J. Poerwowidagdo (2010)
This study examines the linkages between business strategy and high involvement human resource management (HRM) as well as their impact on firm performance. The units of analysis for this study are small and medium enterprises (SMEs) operating in Malaysia. Based on a data set of 42 SMEs, the results show that there were significant relationships among these three major variables: business strategy, high involvement HR practices and firm performance. Significantly, the findings reflect that SMEs which believed in HRM values whereby entrepreneurs viewed people as source of competitive advantage and at the same time, adopted differentiation strategy, were more likely to use high involvement HR strategies. Although differentiation strategies tend to have stronger effects, both differentiation and response speed strategies had significant impact on firm performance. Most importantly, it is proven that SMEs implementation of high involvement HRM strategies significantly correlated with the firm performance.